Identification of high-risk non-ST elevation myocardial infarction at presentation to emergency department. A prospective observational cohort study in North West England. Issue 6 (8th June 2020) - Khand, Aleem; Frost, Freddy; Grainger, Ruth; Fisher, Michael; Chew, Pei; Mullen, Liam; Patel, Billal; Obeidat, Mohammed; Albouaini, Khaled; Dodd, James
Abstract : Objectives: Early access to invasive coronary angiography and revascularisation for high-risk non-ST elevation myocardial infarction (NSTEMI) improves outcomes and is supported by current guidelines. We sought to determine the most effective criteria at presentation to emergency department (ED) to identify high-risk NSTEMI. Setting: Secondary care centre northwest England with national follow-up. Participants: 1642 consecutive patients (median age 59, 52% male) presenting to ED with a primary symptom of chest pain in whom there is suspicion of NSTEMI. Primary and secondary measures: Multivariate logistic regression analysis for the prediction of all-cause death (primary) and major adverse cardiac event (MACE defined as all-cause death, unplanned coronary revascularisation and adjudicated NSTEMI (third universal definition)) (secondary measure) at 1 year. Results: The incidence of adjudicated NSTEMI was 10.7%, and 1-year mortality was 6.3%. Independent predictors for all-cause death at 1 year were Global Registry of Acute Coronary Events (GRACE) >140, age (per decade increase) and high-sensitive cardiac troponin T (hs-cTnT) >50 ng/L. hs-cTnT >50 ng/L was associated with adjudicated index presentation NSTEMI in the greatest proportion of patients (61.7%). When using MACE at 12 months, as opposed to all-cause death, as an end point History, ECG, Age, Risk factors and Troponin (HEART) score ≥7 was included in the multivariate model and had better prediction of index NSTEMI than GRACE>140. Combining hs-cTnT >50 ng/L and a second independent predictor identified both a high proportion of index NSTEMI and elevated risk of all-cause death at 1 year. Conclusions: hs-cTnT >50 ng/L or HEART score ≥7 appear effective strategies to identify high-risk NSTEMI at presentation to emergency room with chest pain. Multicentre prospective studies enriched with early presenters, and with competitor high-sensitive and point-of-care troponins, are required to validate and extend these findings. Trial registration number: NCT02581540 .